Rodzice wobec wyboru formy kształcenia dziecka z niepełnosprawnością - LIPIŃSKA-LOKŚ, JOLANTA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Jolanta Lipińska-Lokś, Rodzice wobec wyboru formy kształcenia dziecka z niepełnosprawnością [Parents against choosing a form of education for a child with a disability]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 305-321. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.17 The law in the situation of a child with disability acquires particular importance, especially in the matter of choosing the form of its education. Whether they will choose a special school or an integration class for their child, or maybe they will think about inclusive education – it is conditioned by many factors, and each of them can be the most important for a particular parent. The subject of the presented research message was made the opinions and experiences of parents in the area of choosing form of education for a child with disability. The settles of their earlier decisions and the level of accuracy of choice were determined thanks to the assessment of a given form of education by the parents.